Reckoning with Millet's "Man with a Hoe", 1863-1900 - Allan, Scott (J. Paul Getty Museum, 2023)
"Situates French artist Jean-François Millet's painting 'Man with a Hoe' (1860-62) in the arc of his career and traces its reception, from its debut at the 1863 Paris Salon to the years following its acquisition by American collectors in the 1890s"--